Il “ragionamento giuridico” di Giuseppe Terranova - Marco Maugeri (2023)
Prof. Terranova’s insightful book on “Legal Reasoning” offers a deep dive into the challenges arising from the “porosity” of legal language. By succinctly analyzing the main theoretical assumptions of the book, this paper highlights how, in Prof. Terranova’s thought, the different modes of legal reasoning play a critical role in the attempt to filter information from the context and overcome the vagueness of normative concepts.